CURRENT STRATEGIES IN DIAGNOSIS OF OBSTRUCTIVE SLEEP APNEA SYNDROME IN CHILDREN WITH OBESITY - Mihaela Roxana Popescu; Roxana Șerban; Otilia Novac; Liliana Barbacariu; Luiza-Simona Pohaci-Antonesei; Elena Rodica Popescu; Letiția Doina Duceac; Oana-Raluca Temneanu (Romanian Journal of Oral Rehabilitation)
Obstructive sleep apnea syndrome (OSAS) in obese children represents a pathology with multiple implications in physical and mental development and also in social life. The implications of untreated OSAS can be disastrous, with both short-term and long-term consequences. Diagnosis and treatment of OSAS in children is a priority. The current study represents a review of the specialized literature from the last 10 years, focusing on the diagnostic methods that can facilitate surgical and non-surgical treatment. The existence of vast tools for exploring OSAS allows a multidisciplinary approach to the pathology, with multiple directions of treatment.